Evaluation of frontline demonstrations on rapeseed (Brassica napus L.) in south western district of Punjab (Journal of Oilseed Brassica, 2026)
Rapeseed-mustard is an important crop of India but its productivity is low due to poor knowledge level of the farmers regarding improved technologies. Frontline demonstrations are important tool for technology transfer to the farmers and its imperative to demonstrate high yielding, nutritionally better varieties to improve productivity. KVK, Sri Muktsar Sahib conducted frontline demonstrations on new canola variety during 2015-16 with the objective to endorse canola, assessment of its performance in the district and to collect farmer’s feedback information. The results obtained from the study revealed that average yield of canola under FLDs was 19.3 q/ha as compare to 15.5 q/ha recorded in farmer’s practice thereby giving average yield increase of 24.2 per cent. Additional investment of Rs 1246 ha-1 along with scientific monitoring of demonstrations resulted in additional return of Rs 13784 ha-1 over farmers practice.